The glycerol backbone of phospholipids derives from noncarbohydrate precursors in starved lung cancer cells - Leithner, Katharina (Proc Natl Acad Sci U S A, 2018)
Cancer cells are reprogrammed to consume large amounts of glucose to support anabolic biosynthetic pathways. However, blood perfusion and consequently the supply with glucose are frequently inadequate in solid cancers. PEPCK-M (PCK2), the mitochondrial isoform of phosphoenolpyruvate carboxykinase (PEPCK), has been shown by us and others to be functionally expressed and to mediate gluconeogenesis, the reverse pathway of glycolysis, in different cancer cells. Serine and ribose synthesis have been identified as downstream pathways fed by PEPCK in cancer cells. Here, we report that PEPCK-M–dependent glycerol phosphate formation from noncarbohydrate precursors (glyceroneogenesis) occurs in starved lung cancer cells and supports de novo glycerophospholipid synthesis. Using stable isotope-labeled glutamine and lactate, we show that PEPCK-M generates phosphoenolpyruvate and 3-phosphoglycerate, which are at least partially converted to glycerol phosphate and incorporated into glycerophospholipids (GPL) under glucose and serum starvation. This pathway is required to maintain levels of GPL, especially phosphatidylethanolamine (PE), as shown by stable shRNA-mediated silencing of PEPCK-M in H23 lung cancer cells. PEPCK-M shRNA led to reduced colony formation after starvation, and the effect was partially reversed by the addition of dioleyl-PE. Furthermore, PEPCK-M silencing abrogated cancer growth in a lung cancer cell xenograft model. In conclusion, glycerol phosphate formation for de novo GPL synthesis via glyceroneogenesis is a newly characterized anabolic pathway in cancer cells mediated by PEPCK-M under conditions of severe nutrient deprivation.